Correction: HIV microarray for the mapping and characterization of HIV-specific antibody responses. Issue 2 (9th December 2015) - Gallerano, Daniela; Wollmann, Eva; Lupinek, Christian; Schlederer, Thomas; Ebner, Daniel; Harwanegg, Christian; Niespodziana, Katarzyna; Schmetterer, Klaus; Pickl, Winfried; Puchhammer-Stöckl, Elisabeth; Sibanda, Elopy; Valenta, Rudolf
Abstract : Abstract : Correction for 'HIV microarray for the mapping and characterization of HIV-specific antibody responses' by Daniela Gallerano et al., Lab Chip, 2015, 15, 1574–1589.